(untitled) (European Journal of Marketing and Economics, 2024)
In combination with sluggish economic development, the financial crisis and the debt crisis that it triggered have contributed to the fact that tax evasion, tax fraud and tax avoidance are recognized as a serious problem. Tax evasion and tax fraud by well-known personalities from politics, sport, the arts and commerce also attract intensive coverage in the media. In the companies sector, internationalization makes it easier for global corporations to shift their profits to low-tax countries and thus to minimize their tax bill. This paper shall discuss also, the measures to combat international tax evasion to be worked out by the OECD and the G20. The fact that multinational corporations are able to reduce their tax burden on profits through tax-saving plans has been known for decades. There are several reasons for the massive increase in this phenomenon in recent years. On the one hand there has been increasing globalisation, on the other corporate structures have also changed massively in recent decades. Tax havens play an important role in this context and there is practically no global player without branches in tax havens.